Richard II Drama von William Shakespeare - Shakespeare, William (Opus Arte, 2014)
Richard is King. A monarch ordained by God to lead his people. A man whose vanity threatens to divide the great houses of England and drag his people into a dynastic and bloody civil war that will last 100 years. RSC Artistic Director Gregory Doran directs David Tennant in the little role of 'a definitive production of a great play'. [Cover]